TOKOH-TOKOH DAN PEMIKIRAN FILSAFAT DUNIA BARAT - Fitria Dwi Rahmawati; Lailatul Mubarokah; Mohammad Asrori; Ayu Wilatikta (Raudhah - Proud To Be Professional, 2022)
Education in Indonesia is a form of contribution to the thoughts of Western world philosophers. Before education was known, human civilization became the main study in the birth of a science. With him education and history have a close and inseparable relationship. Philosophical figures have contributed many thoughts related to education. Therefore these figures are very worthy to be studied in the world of education. There are two philosophical figures themselves, namely the philosophers of the western and eastern worlds. This research uses a qualitative type approach with a descriptive method. The source of the study in this study used a research library. The purpose of this study is to find out the philosophical figures of the western world and their thoughts. The result of this research is that there are many philosophers who introduce their thoughts. There are about 100 philosophers listed in a study, but only a few whose thoughts are considered relevant include Thales, Pythagoras, Xenopanes, Socrates, Plato, and Aristotle.